Application of L-series of Formation in Fuzzy Pattern Recognition - Jinhong Li; Kangpei Zhao (Institute of Advanced Engineering and Science, 2014)
In this paper, the model base and objects to be identified are classed as information granules by the information granulation idea. A proper system of polar coordinates is established. The fuzzy pattern recognition problem is studied by the L-series of formation in the abstract analytic number theory. A method is given to evaluate the model base type of the information granules, which consist of massive data. Additionally，it is used to analyze the relation between process parameters and weld appearance in the welding process. At the same time, the relations between weld appearance and process parameters are studies by the rough set and the disposal of data discretization based on attribute-priority algorithm. The results with these two methods are coincident. The method proposed in this paper is proved to be true. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4521